Beberapa Faktor yang Mempengaruhi Kepuasan Karyawan pada Swalayan Purnama - Kasnowo; Anindita Imam Basri; Anisa Wijaya Putri (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This research was conducted at the Purnama Godean Supermarket, the focus of this research was on three dependent variables with the aim of knowing the effect of motivation, discipline, and organizational commitment on employee job satisfaction with quantitative research methods. The number of samples is 77 people using saturated sampling technique. While the data collection is done by means of interviews and questionnaires. The data analysis technique used multiple linear regression analysis which was processed with the SPSS program. The results showed that partially work motivation had an effect on job satisfaction with a sig value of 0.032 < 0.05, work discipline had an effect on job satisfaction with a sig value of 0.008 < 0.05, organizational commitment had an effect on job satisfaction with a sig value of 0.000 < 0.05. The results of the simultaneous test of motivation, discipline, and organizational commitment have an effect on employee satisfaction as indicated by a sig value of 0.000 <0.05.